Erosion wear resistance mechanism of erosion ripples. (October 2022) - Zhang, Yan; Zhao, Xuwen; Wang, Qi; Wang, Tianqi; Tang, Yuling
Erosion ripples widely exist on natural and industrial surfaces suffering gas–solid flow erosion. During the steady state of erosion ripples formation, the material removal and plastic flow rate of the material basically reach a dynamic equilibrium. In this state, the erosion rate of the surface material is steady and at a low level. In this paper, the relationship between erosion ripples and the erosion characteristics of surface materials was explored by experimental and simulation methods. Under the conditions of air pressures of 0.3, 0.4 and 0.5 MPa and erosion angles of 30°, 40° and 50°, several erosion ripples were prepared on the surface of 1060 aluminium alloy samples by sandblasting. According to the obtained morphological parameters and orthogonal test design, rippled samples with rectangular, triangular and semicircular groove sections were designed. The effect of morphology parameters on the erosion resistance of the sample was analysed by a sandblasting test. The results showed that the rippled samples have lower erosion rates than the plate sample. The cross-sectional shape of grooves is the most obviously affected factor. The velocity distribution and surface pressure distribution on the surface of rippled and plate samples were analysed by FLUENT software, and the results showed that the low-speed reflow vortex will be formed in grooves of erosion ripples that can change the near-wall flow field conditions. The differential pressure generated on two sides of the ridge between adjacent grooves, as well as the area decrease of erosion caused by the "shaded effect, " may be the cause of the erosion resistance. The results of this study can provide new insight into the active erosive wear resistance method of mechanical components.